Mapping of Disability Management Publications Using Bibliometric Analysis - Prasetya, Budi Agung; Tunas, Billy; Parimita, Widya; Setiawan, Adi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to identify scientific mapping and research developments related to Disability Management. Research related to disability management is needed to guide the implementation of disability management. The research method used a qualitative method using a historical approach. The research data were articles published by reputable journal publishers that use the Publish or Perish (PoP) application. Data analysis used bibliometric analysis assisted by VOSviewer. The bibliometric output visualized the keyword network and maps obtained from the titles and abstracts contained in the collected articles. The study results showed that the mapping and development of studies related to stability management are as follows: First, the publication trend of articles related to disability management which began in 1987, experienced fluctuating conditions. The data showed that research related to disability management was starting to receive attention from academics. Second, the results of the co-authorship analysis showed that there were 149 collaborating on research. Eleven authors carried out the most significant collaborations. The most articles produced by the author are seven articles. This condition showed the authors' high commitment to continue developing knowledge related to disability management. Third, a Network Visualization analysis with VOSviewer software produced 133 keywords related to stability management. These keywords were divided into 11 clusters. Keywords that were often researched were related to "intellectual disability", "perspective", "equity", "organization", "fairness", "risk, individual", "competence", "management disability practice" and "disability prevention".